MEMBANGUN KARAKTER BANGSA MELALUI PEMBELAJARAN MATEMATIKA KURIKULUM 2013 - wahyudin wahyudin (LPPM Universitas Terbuka, 2013)
The development of the character education still becomes the controversy among the educators, either from the theoretical or philosophical points of view. Actually, the core of the character education is not only viewed from philosophical difference, pedagogical ideology, or politics, but focused on the child development. Curriculum 2013 seeks to provide a problem-solving on the cultural matters and the national characters by integrating the characters / values /attitudes into the lessons, self-development, and the culture of the school. It is expected that a new generation of nation is developed in attitudes, knowledge, and skills. It has been clear that teachers thought, beliefs, and choices will influence their teaching practice. Therefore, it is necessary to build the views, beliefs, and positive selection within the teachers mind for the successful implementation of Curriculum 2013. Perkembangan pendidikan karakter sampai sejauh ini masih penuh dengan kontroversi yang terutama berakar dalam berbagai perbedaan teoretis dan filosofis, meski sebenarnya inti dari pendidikan karakter tidak pada perbedaan filosofis, ideologi pedagogis, politik, dan sebagainya, melainkan tentang perkembangan anak. Kurikulum 2013 berupaya memberikan pemecahan persoalan budaya dan karakter bangsa dengan cara mengintegrasikan karakter/nilai/sikap ke dalam mata pelajaran, pengembangan diri, dan budaya sekolah, dengan harapan terbentuknya generasi baru bangsa yang utuh dalam sikap, pengetahuan, dan keterampilan. Dengan menyadari bahwa pandangan, keyakinan, dan pilihan para guru akan berpengaruh pada praktek pembelajaran, maka perlu dibangun pandangan, keyakinan, dan pilihan yang positif dalam diri para guru demi keberhasilan implementasi Kurikulum 2013.